Feminism Analysis in the Novel “The Blue Castle” by L.M. Montgomery - Kurniati, Nia; Sabilah, Dina; Ulwiyah, Fina; Septiani, Ni Kadek Ely (Universitas Muhammadiyah Mataram, 2025)
Feminism was a movement that seeks justice, liberation and equality between men and women in all areas advocating for women's rights and priorities. In addition, the role of female characters was often portrayed as oppressed individuals compared to men, including in their work, education, and roles in society. This research used a qualitative descriptive method. The novel “The Blue Castle” told the story of a woman named Valency Stirling in the face of oppression and pressure in her family and society. This research described feminism, the struggle of a woman in fighting for her rights contained in the novel. The purpose of this study was to explore the theory of feminism and raise awareness of social issues, especially for women in society. The results of this study found forms of injustice or oppression in the family/society to Valency, the courage to live a free life, and the awareness that makes Valency happier with her life based on the perspective of feminism.